Erectile dysfunction following radiotherapy and brachytherapy for prostate cancer: pathophysiology, prevention and treatment - ŞİMŞEK, FERRUH; TİNAY, İLKER (SPRINGER, 2008)
Objectives Although detrimental impact on sexual function following radiotherapy (RT) and brachytherapy decreases the quality of life of prostate cancer survivors, the etiology, pathophysiology, prophylaxis and treatment of this condition has not yet been fully clarified. We reviewed the published literature in terms of etiology, treatment and possible prevention of erectile dysfunction (ED) following RT and/or brachytherapy. Method We have reviewed the literature through a MEDLINE search. Prostate cancer, erectile dysfunction, radiotherapy, brachytherapy, treatment and quality of life were used as keywords. Conclusion Both RT and brachytherapy result in high rates of ED. Although arterial damage seems to be the main cause of ED after RT, exposure of neurovascular bundle to high levels of radiation dose has been also implicated in some studies with brachytherapy. The radiation dose received by the corpora cavernosa at the crurae of the penis may also be important in the etiology of ED. The most important predictive factor of ED following RT is the treatment modality. Intensity-modulated radiotherapy and vessel-sparing prostate radiotherapy are new techniques but those treatments may not guarantee complete preservation of the erectile function. Patients need to be correctly informed on the possible sequela of radiation-based treatments on their sexual well-being while planning their treatment. Patients should also be informed about the possible treatment modalities for ED, which may develop in due course.
Keywords: brachytherapy; erectile dysfunction; prostate carcinoma; radiotherapy; treatment; 3-DIMENSIONAL CONFORMAL RADIOTHERAPY; QUALITY-OF-LIFE; EXTERNAL-BEAM RADIATION; SILDENAFIL CITRATE VIAGRA; SEXUAL FUNCTION; RADICAL PROSTATECTOMY; DOUBLE-BLIND; PENILE BULB; THERAPY; EFFICACY